Problemas emocionales y de conducta asociados al confinamiento por pandemia COVID 19 en escolares de la Unidad Educativa Pío Jaramillo Alvarado - Armijos Ochoa, Omailee Jamileth (2024)
COVID-19 has caused different changes in the world population, one of them has occurred in the population of children, since they are in a total alteration of the rhythm of their lives, beginning with the closure of schools and with changes in family dynamics, interaction with their peers and their routines among others, this is producing a psychological impact on them that can become exacerbated and produce greater consequences. One in seven children suffers from mental health problems, mainly depression, anxiety and post-traumatic stress disorder. Therefore, this research was developed with a quantitative approach, descriptive type and transversal design, with the objective of establishing the emotional and behavioral problems associated with confinement due to the COVID-19 pandemic in schoolchildren from the Pio Jaramillo Alvarado Educational Unit. A total of 173 children who met the inclusion and exclusion criteria, the difficulties and abilities questionnaire was applied to both children and their parents. The result is that 15.03% present abnormal behavior, that is, with the presence of psychopathology, and 19.08% show borderline behavior, of which the majority presented emotional symptoms with 47.98%, 19.08% hyperactivity problems, problems with peers and behavioral problems such as frustration and tantrums, lack of obedience, frequent aggression. Regarding family functionality, 60.12% classify their family as moderately functional. When establishing the relationship between these two variables, it was found that there is a statistically significant relationship. Based on the results of this research, it was identified that confinement affected the mental health of children, triggering multiple emotional and behavioral problems, consequently, altering family coexistence